2016
DOI: 10.1016/j.jtcme.2014.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin improves liver damage in male mice exposed to nicotine

Abstract: The color of turmeric (薑黃 jiāng huáng) is because of a substance called curcumin. It has different pharmacological effects, such as antioxidant and anti-inflammatory properties. Nicotine is a major pharmacologically active substance in cigarette smoke. It is mainly metabolized in the liver and causes devastating effects. This study was designed to evaluate the protective role of curcumin against nicotine on the liver in mice.Forty-eight mice were equally divided into eight groups; control (normal saline), nico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 33 publications
3
59
1
Order By: Relevance
“…Ricky et al have demonstrated that liver is pharmacological targets of dietary curcumin (Sharma et al, ). Salahshoor et al have found that curcumin (60 mg/kg BW) improves nicotine‐triggered liver damage in male mice (Salahshoor et al, ). Before feeding, curcumin was reformulated with corn oil in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Ricky et al have demonstrated that liver is pharmacological targets of dietary curcumin (Sharma et al, ). Salahshoor et al have found that curcumin (60 mg/kg BW) improves nicotine‐triggered liver damage in male mice (Salahshoor et al, ). Before feeding, curcumin was reformulated with corn oil in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Every eight mice were grouped together forming four differently treated groups: Group I mice (control group) received tap water administered by gastric gavage at a dose of 1 ml/100 g body weight 1 hr before and 1 hr after each mouse was intraperitoneally injected with a phosphate buffered saline. Group II mice received GT solution administered by gastric gavage at a dose of 1 ml/100 g body weight twice a day 1 hr before and 1 hr after nicotine injection. Group III mice were injected intraperitoneally with nicotine (2.5 mg/kg) once per day and received tap water orally at a dose of 1 ml/100 g body weight 1 hr before and 1 hr after nicotine injection via gastric gavage. Group IV mice received both nicotine and GT. GT administered 1 hr before and 1 hr after nicotine injection via gastric gavage, treatment with nicotine dosage was based on a previous study (Salahshoor, Mohamadian, Kakabaraei, Roshankhah, & Jalili, ). …”
Section: Methodsmentioning
confidence: 99%
“…Group IV mice received both nicotine and GT. GT administered 1 hr before and 1 hr after nicotine injection via gastric gavage, treatment with nicotine dosage was based on a previous study (Salahshoor, Mohamadian, Kakabaraei, Roshankhah, & Jalili, 2016).…”
Section: Experimental Designmentioning
confidence: 99%
“…[25,26] Curcumin Curcumin (Curcuma longa) possesses various biological activities such as anti-inflammatory, hepatoprotective, antibacterial, antidiabetic, antidepressant, analgesic, and anticarcinogenic. [27,28] The anti-inflammatory action of curcumin is attributed to inhibition of LOX, suppression of activation of NF-β, TNF-α, molecular adhesion, and inhibition of upregulation of matrix metalloproteinase (MMP-9) mRNA. It also promotes suppression of expression of TNF-α-induced MMP-13 in chondrocytes.…”
Section: Herbal Productsmentioning
confidence: 99%